Electrical stimulation—a mapping system for hand dysfunction in tetraplegia. Issue 5 (May 2018) - Bersch, Ines; Koch-Borner, Sabrina; Fridén, Jan
Abstract Study design Retrospective data analysis Objectives To define the distribution of the motor points and excitability of the key wrist and finger actuators in order to detect upper (UMN) and lower motor neuron (LMN) lesions potentially influencing the development of a tenodesis grasp. Setting A rehabilitation centre for spinal cord injuries, Nottwil, Switzerland. Methods Forearm muscles of 32 patients with tetraplegia (AIS A–D) were tested bilaterally with electrical stimulation (ES) to differentiate whether UMN or LMN was present. For testing, a standardised mapping was developed. All patients underwent the same positioning schedule. Results Sixteen hands developeda tenodesis grasps, 24 hands showed neither shortening nor tightening of the finger flexors. Two patients developed unilateral tenodesis grasp and showed no tightening of the finger flexors on the contralateral hand. Seven patients developed tenodesis grasps symmetrically and bilaterally, whereas one maintained an essentially open hand without tightening of the finger flexors. All hands that developed a tenodesis grasp showed a LMN lesion of the M. extensor digitorum communis (EDC). The frequency of the tenodesis grasp differed significantly between the groups with and without intact reflex arc (p  < 0.0001). Conclusion Surface ES may serve as a diagnostic tool to detect an UMN or LMN lesion of the key actuator muscles affecting the tenodesis grasp. These findings provide information that is essential for the choice of treatment to optimise function of the tetraplegic hand.